A Comparison Study of the Fitbit Activity Monitor and PSG for Assessing Sleep Patterns and Movement in Children - Osterbauer, Beth; A. Koempel, Jeffrey; L. Davidson Ward, Sally; M. Fisher, Laurel; M.Don, Debra (Journal of Otolaryngology Advances, 2016)
Background: Despite its expense, labor and intrusiveness, polysomnography (PSG) is the gold standard for diagnosing obstructive sleep apnea (OSA). Recently, commercially available electronic activity monitors, such as Fitbit, have become widely accepted and can provide an estimate of sleep patterns for screening children with possible OSA. A previous study demonstrated Fitbit to be valid compared to PSG in adults. To date, these devices have not been extensively utilized for research in children with sleep disordered breathing (SDB). Objective: To evaluate the validity of the Fitbit activity monitor compared to PSG in children and adolescents with SDB. Methods: Data was collected from 14 children, ages 3 through 11, who were scheduled for a PSG during the study period. Fitbit was worn concurrently during the night of the PSG. Analyses were performed by comparing total sleep time, number of awakenings, sleep efficiency and wake after sleep onset (WASO) Fitbit parameters with the corresponding parameters measured by PSG using Spearman’s rho. Fitbit movement epochs were also compared to PSG epochs showing movement behavior. Results: Pilot data suggest that Fitbit demonstrates a high sensitivity for sleep, a low specificity for wake and a trend suggesting good association of movement measurements. Conclusion: Although Fitbit is not as accurate as PSG for determining wakefulness, it may be a useful screening device to assess gross sleep quality in children. Further studies are indicated to validate these findings.
Keywords: Pediatric; sleep disordered breathing; activity monitor; obstructive sleep apnea; actigraphy; polysomnogram